Legal Analysis of Public Prohibition on Railway Tracks in Indonesia: Analisis Hukum Larangan Umum di Rel Kereta Api di Indonesia - Sari, Ana Firda; Phahlevy, Rifqi Ridlo (Indonesian Journal of Law and Economics Review, 2025)
General Background: The railway system serves as a vital component of public transportation supporting human mobility and logistics. Specific Background: However, persistent violations of the prohibition against being on railway tracks remain a serious safety issue in Indonesia, particularly in suburban and rural regions. Knowledge Gap: Despite the existence of Law Number 23 of 2007 concerning Railways, limited studies have examined the law’s juridical interpretation and its uneven enforcement between urban and rural areas. Aims: This study aims to analyze the legal basis, enforcement barriers, and implementation differences regarding the prohibition of being on railway tracks. Results: Findings reveal that enforcement is more consistent in urban settings due to stronger supervision and infrastructure, while rural areas face challenges stemming from weak law enforcement, poor coordination, and low legal awareness. Novelty: This research provides a juridical and comparative insight into the disparities in legal application across regions. Implications: Strengthening safety infrastructure, community legal education, and interagency coordination are essential to achieve legal compliance and public safety in railway operations. Highlights: Law enforcement is stronger in urban areas than in rural ones. Legal awareness and safety infrastructure remain key challenges. Coordination among authorities is vital for public railway safety. Keywords: Railway Law, Legal Prohibition, Public Safety, Law Enforcement, Indonesia